2020
DOI: 10.1210/endocr/bqaa013
|View full text |Cite
|
Sign up to set email alerts
|

Role for Kisspeptin and Neurokinin B in Regulation of Luteinizing Hormone and Testosterone Secretion in the Fetal Sheep

Abstract: Evidence suggests that the hypothalamic–pituitary–gonadal (HPG) axis is active during the critical period for sexual differentiation of the ovine sexually dimorphic nucleus, which occurs between gestational day (GD) 60 and 90. Two possible neuropeptides that could activate the fetal HPG axis are kisspeptin and neurokinin B (NKB). We used GD85 fetal lambs to determine whether intravenous administration of kisspeptin-10 (KP-10) or senktide (NKB agonist) could elicit luteinizing hormone (LH) release. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The early study demonstrated that several physiological factors both directly and indirectly relay their impacts on GnRH neurons; therefore, short-term regular moderate and intensive exercises may exert their effects directly or indirectly. Numerous studies have addressed the role of KNDy neurons in reproduction and have emphasized the key role of this neuropeptide in projecting the effects of various factors on releasing GnRH/LH (Amodei et al, 2020;Yeo and Colledge 2018). Accordingly, the present research studied changes in the mRNA level of the arcuate neuropeptide (upstream of GnRH neurons) in response to short-term moderate and intensive physical activity.…”
Section: A B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early study demonstrated that several physiological factors both directly and indirectly relay their impacts on GnRH neurons; therefore, short-term regular moderate and intensive exercises may exert their effects directly or indirectly. Numerous studies have addressed the role of KNDy neurons in reproduction and have emphasized the key role of this neuropeptide in projecting the effects of various factors on releasing GnRH/LH (Amodei et al, 2020;Yeo and Colledge 2018). Accordingly, the present research studied changes in the mRNA level of the arcuate neuropeptide (upstream of GnRH neurons) in response to short-term moderate and intensive physical activity.…”
Section: A B Discussionmentioning
confidence: 99%
“…On the other hand, although recent studies in rodents have reported contradictory effects of the NKB on GnRH and LH secretions (Rance et al, 2010), most of the investigations have suggested that the NKB had an inhibitory effect on LH secretion in rodents with high levels of sex steroid hormones. The NKB agonist acted as an inhibitor of LH secretion in both rats and mice (Amodei et al, 2020;Chaikhun et al, 2013;Grachev et al, 2012).…”
Section: A B Discussionmentioning
confidence: 99%
“…A similar situation is observed in the female goat with a stimulatory effect of the iv administered NKB agonist (senktide) (103) or no effect of the icv injected NKB (177), regardless of the gonadal status. Recently, iv administration of senktide has even been shown to be efficient in stimulating LH release in fetal male and female sheep (211). In humans, early studies report no gonadotropin-stimulating effect of NKB iv administered in adult men and women (212,213), but a series of data obtained by Skorupskaite and collaborators using the TACR3 antagonist given orally show a decrease in overall circulating LH levels and LH pulsatility in adult men (214) and women (215)(216)(217).…”
Section: Mammalsmentioning
confidence: 99%
“…Tachykinins and their receptors are also expressed in the stomach and intestine of many teleosts, suggesting potential autocrine or paracrine actions [zebrafish (26,71); tilapia (72); goldfish (73,88); grass carp (61,75,211); orange-spotted grouper (77); spotted sea bass (78); tongue sole (79)].…”
mentioning
confidence: 99%